Creative Behavior in the Online Fashion Business - Ratih Indriyani; Kevin Christanto (MediaTrend, 2022)
Fashion secror has been increasing in Indonesia.Creativity is important thing for an online business to be able to survive and compete in the digital market. Some variables that can improve creative behavior are accurate market orientation and effective use of social media. The purpose of the research is to analyze the influence of market orientation and social media usage on creative behavior in online businesses in the fashion sector in Surabaya. By using purposive sampling method, 132 online businesses in the fashion sector in Surabaya have been selected as respondents. This research used quantitative approach of this explanatory using partial least square. Result of this study describe that market orientation  has a significant influence on creative behavior, on the other side, social media usage has usage has a significant influence on creative behavior . This research also show that market orientation  has significant influence on creative behavior throug social media usage  among online businesses fashion sector in Surabaya.